2015
DOI: 10.1103/physrevb.92.134412
|View full text |Cite
|
Sign up to set email alerts
|

Fragile magnetic order in the honeycomb lattice IridateNa2IrO3revealed by magnetic impurity doping

Abstract: We report the structure, magnetic, and thermal property measurements on single crystalline and polycrystalline samples of Ru substituted honeycomb lattice iridate Na2IrxRu1−xO3 (x = 0, 0.05, 0.1, 0.15, 0.2, 0.3, 0.5). The evolution of magnetism in Na2IrxRu1−xO3 has been studied using dc and ac magnetic susceptibility, and heat capacity measurements. The parent compound Na2IrO3 is a spin-orbit driven Mott insulator with magnetic order of reduced moments below TN = 15 K. In the Ru substituted samples the antifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…f changing from 100 to 10000 Hz. This value is close to those observed in other insulating spin glasses [34][35][36][37][38]. The strong frequency dependence evidences a broad distribution of the spin relaxation times around T f , typical for a spin glass [34][35][36].…”
supporting
confidence: 88%
“…f changing from 100 to 10000 Hz. This value is close to those observed in other insulating spin glasses [34][35][36][37][38]. The strong frequency dependence evidences a broad distribution of the spin relaxation times around T f , typical for a spin glass [34][35][36].…”
supporting
confidence: 88%
“…A maximum is observed at 0.33 K which is too broad to indicate a phase transition to long-range magnetic order. This peak shifts by 0.015 K over the entire frequency range (Mydosh parameter φ = 0.022), such a shift is typical either for an insulating spin-glass or the presence of slow dynamics [30].…”
mentioning
confidence: 90%
“…Experimental studies on honeycomb iridates showed that the substitution of Ir 4+ by nonmagnetic ions, such as Ti 4+ in Li 2 Ir 1−x Ti x O 3 and Na 2 Ir 1−x Ti x O 3 , and also by strongly spin-orbit-coupled magnetic ions, e.g. Ru 4+ in Na 2 Ir 1−x Ru x O 3 , changes the antiferromagnetic zigzag state into a spin-glass state 34,35 . Via Monte Carlo calculations on the Kitaev-Heisenberg model this formation of a spin-glass state under the substitution of the magnetic ion by a nonmagnetic ion 36 or by magnetic ions 37 has successfully been rationalized.…”
Section: Introductionmentioning
confidence: 99%